2018
DOI: 10.1111/cod.13150
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis caused by cysteamine hydrochloride in permanent wave agent—A new allergen for hairdressers in Japan

Abstract: In addition to the Japanese baseline allergen series version 2008,11 we used cysteamine HCl 1% and 0.5% pet. (Table S1). We also included the participants' own perming solutions, as used by them at the salon, for open tests. RESULTSDetails of the 3 male and 4 female hairdressers, ranging in age from 22 to 73 years, are shown in Table S2. Regarding the cysteamine HCl patch tests, 5 patients showed positive reactions to both 1% and 0.5%. One patient showed a positive reaction to 1% alone, and the other patient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…Although cysteamine is typically more expensive than other reducing agents such as thioglycolic acid and cysteine, cysteamine has the following advantages as a cosmetic ingredient: 1) reduction can occur at a more neutral pH and 2) less hair damage occurs compared with conventional reducing agents (20). Cases of cysteamine-induced allergic contact dermatitis are rare, but some patch test studies demonstrated positive results (7,8). Among 1,347 hairdressers patch-tested with 0.5% cysteamine, 16 clinically relevant positive reactions (1.2%) were observed from 1994 to 2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although cysteamine is typically more expensive than other reducing agents such as thioglycolic acid and cysteine, cysteamine has the following advantages as a cosmetic ingredient: 1) reduction can occur at a more neutral pH and 2) less hair damage occurs compared with conventional reducing agents (20). Cases of cysteamine-induced allergic contact dermatitis are rare, but some patch test studies demonstrated positive results (7,8). Among 1,347 hairdressers patch-tested with 0.5% cysteamine, 16 clinically relevant positive reactions (1.2%) were observed from 1994 to 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Among 1,347 hairdressers patch-tested with 0.5% cysteamine, 16 clinically relevant positive reactions (1.2%) were observed from 1994 to 2004. Recently, allergic contact dermatitis was assessed in 17 hairdressers in Japan, and 7 of these individuals had allergic reactions to cysteamine (8). Therefore, cysteamine may need to be included in a test series with hair waving and dyeing agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neben dem „klassischen“ Wirkstoff Ammoniumthioglykolat wird zunehmend auch Cysteaminhydrochlorid eingesetzt, und bei 7/17 japanischen Friseuren in einem Zentrum wurde es als Allergen getestet (positiv auf 0,5 % und 1 % pet.) [227].…”
Section: Ergebnisseunclassified
“…Besides the "classical" agent ammonium thioglycolate, cysteamine hydrochloride has been increasingly used and reported as an allergen in 7/17 Japanese hairdressers tested in one department (positive to 0.5% and 1% pet.) [227].…”
Section: Medicines (Active Principles and Excipients) And Cosmeticsmentioning
confidence: 99%